A comparative histopathological, immunological, and biochemical study of experimental intravenous paracoccidioidomycosis induced in mice by three paracoccidioides brasiliensis isolates - Zacharias, Darwin; Ueda, Anete; Moscardi-Bacchi, Maura; Franco, Marcello; San-Blas, Gioconda (Oxford University Press (OUP), 1986)
We carried out a comparative study of the histopathology (lung, liver, spleen, kidney and adrenals) and the anti-P. brasiliensis humoral (immunodiffusion test) and cellular (footpad test) immune response of mice intravenously inoculated with yeast forms of three P. brasiliensis isolates (Pb 18, Pb 192, Pb 265). Pb 265 (avirulent strain) did not evoke specific lesions or antibody production; the levels of cellular immunity were significantly lower than those of the two other isolates. Lung granulomas induced by strain Pb 18 were richer in fungi and neutrophils and poorer in mononuclear cells when compared to those induced by strain Pb 192. Extrapulmonary lesions were more frequent in mice infected with strain Pb 18. Strains Pb 18 and Pb 192 raised similar humoral and cellular anti-P. brasiliensis responses. Cell wall analysis did not suggest striking differences among the strains. Slightly higher levels of the water soluble fraction 3 (which contains the immunogenic galactomannan and protein) were detected in strain Pb 265. © 1986 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.